A bioorthogonal click chemistry toolbox for targeted synthesis of branched and well-defined protein-protein conjugates - Baalmann, Mathis; Neises, Laura; Bitsch, Sebastian; Schneider, Hendrik; Deweid, Ludwig Lukas; Ilkenhans, Nadja; Wolfring, Martin; Ziegler, Michael J.; Werther, Philipp; Wilhelm, Jonas; Kolmar, Harald; Wombacher, Richard (ChemRxiv, 2019)
A highly efficient technology for protein functionalization with commonly used bioorthogonal motifs for Diels-Alder cycloaddition with inverse electron demand (DAinv). With the aim of precisely generating branched protein chimeras, we systematically assessed the reactivity, stability and side product formation of various bioorthogonal chemistries directly at the protein level. We demonstrate the efficiency and versatility of our conjugation platform using different functional proteins and the therapeutic antibody trastuzumab. This technology enables fast and routine access to tailored and hitherto inaccessible protein chimeras useful for a variety of scientific disciplines.